A pastoral frontier: From chaos to capitalism and the re-colonisation of the Kazakh rangelands. (April 2016) - Kerven, Carol; Robinson, Sarah; Behnke, Roy; Kushenov, Kanysh; Milner-Gulland, E.J.
Abstract: There is little research on pastoralists' responses to new expansion opportunities. We explore how pastoralists in Kazakhstan have responded to rapid, fundamental institutional and macroeconomic changes. We compare use patterns of grazing and water sites in two periods; 1999–2003, after the collapse of the Soviet Union, when the rural economy was in crisis and 2012–14, following a recovery in livestock numbers and a boost in the national economy. The study uses historical studies, formal surveys and anthropological interviews to document changes in livestock ownership, management and selection of pasture and water sites. In 2012–14, owners of the largest flocks had extended their grazing sites further away from the settled villages, moving away from more densely used sites more easily accessed in the 1990s. These new pastoral elites are colonising abandoned state-owned pastures and wells developed by Soviet state farms. Smaller-scale livestock owners based in villages are now less able to entrust their animals to larger-scale owners at remote desert sites, a change since the early post-Soviet period. The economic recovery of Kazakhstan has encouraged pioneering moves by entrepreneurial individuals, moves permitted by post-Soviet laws for privatised pasture land tenure. This expansionist movement parallels ecological patterns of site sequencing in wildlife. Highlights: Kazakh pastoralists' response to recent institutional and macroeconomic changes. Research compares use of pasture land and wells in 1999–2003 and 2012–2014. New elites are colonising abandoned state-owned remote pastures and wells. These moves are permitted by post-Soviet laws for privatised pasture land tenure. Entrustment of livestock is declining from smaller to larger owners at remote sites.